Pelatihan dan Pendampingan Pengelolaan Keuangan pada Amal Usaha Muhammadiyah (AUM) Pendidikan di Kabupaten Ngawi dalam Mewujudkan Pengelolaan Keuangan Sekolah yang Akuntabel : Pengabdian - Nur Sayidatul Muntiah; Nurul Hidayah; Choirul Hamidah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The financial governance of Muhammadiyah's Charity Enterprises (AUM) needs to be improved through joint studies and coordination. Based on initial observations, the AUM budget management system in schools is still partial and unsustainable. This indicates the need for the preparation of financial reports in accordance with accounting standards to ensure more accountable AUM financial management. The community service partner in this activity is Muhammadiyah University of Ponorogo. This program aims to improve the quality and standardization of AUM finances in the education sector to meet the principles of accountability, responsibility, and transparency. The activity was carried out through a Short Accounting Course for Muhammadiyah school treasurers in Ngawi City to improve the ability to prepare good and correct financial reports. The activity methods include: 1) AUM accounting training, 2) Mentoring school treasurers, 3) Student data collection, bills, and graduation policies to prevent the accumulation of diplomas and receivables, 4) Training in the implementation of internal control systems. It is hoped that treasurers can optimize the use of this application to realize accountable and transparent financial management.